Improved photoresponse performance of a self-powered Si/ZnO heterojunction ultraviolet and visible photodetector by the piezo-phototronic effect. (4th May 2017) - Yin, Bing; Qiu, Yu; Zhang, Heqiu; Luo, Yingmin; Zhao, Yu; Yang, Dechao; Hu, Lizhong
Abstract: In this work, we report the fabrication of self-powered Si/ZnO heterojunction ultraviolet and visible photodetectors (PDs) with different doping concentrations. The PDs have a fast response time (shorter than 0.13 s) to the ultraviolet and visible illumination at 0 V bias. The photocurrent of Sample A (high doping concentration) is more than 20 times larger than Sample B (low doping concentration) under 365 nm illumination and more than 150 times larger than Sample B under 450 nm illumination. The larger photoresponse is attributed to the stronger built-in electric field of Si/ZnO heterojunction. Furthermore, we demonstrate the impact of the piezo-phototronic effect for the self-powered Si/ZnO heterojunction ultraviolet and visible photodetector. Under a 0.7N compressive strain, the maximal UV and visible photocurrents are enhanced by about 33.7% and 13.9% for sample A (high doping concentration), about 67.3% and 74.5% for sample B (low doping concentration), respectively. The possible working principle is that the positive piezoelectric charges at the Si/ZnO interface lower the local energy band level of ZnO, thus strengthening the built-in electric field and shift the depletion region to the Si side leading to an increase in the photon-absorption volume. This work may provide a potential approach to enhance the performance of the self-powered Si/ZnO heterojunction ultraviolet and visible photodetector.